2022
DOI: 10.3389/fgene.2022.875013
|View full text |Cite
|
Sign up to set email alerts
|

Novel CNNM2 Mutation Responsible for Autosomal-Dominant Hypomagnesemia With Seizure

Abstract: CNNM2 is primarily expressed in the brain and distal convoluted tubule (DCT) of the kidney. Mutations in CNNM2 have been reported to cause hypomagnesemia, seizure, and intellectual disability (HSMR) syndrome. However, the clinical and functional effect of CNNM2 mutations remains incompletely understood. We report our clinical encounter with a 1-year-old infant with HSMR features. Mutation screening for this trio family was performed using next-generation sequencing (NGS)-based whole exome sequencing (WES) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The kidney and the intestinal tract are the principal organs involved in Mg homeostasis. Mutations affecting the intestinal and renal transport of Mg 2+ ions like transient receptor potential cation ( TRPM6 ), pterin-4-alpha carbinolamine dehydratase 1 ( PCBD1 ) or cystathionine-β-synthase-pair domain divalent metal cation transport mediator 2 ( CNNM2 ) gene can lead to HSH 4–6. Hypomagnesaemia causes hypocalcaemia by three mechanisms: end-organ unresponsiveness to PTH, impaired release of PTH and impaired formation of 1,25-dihydroxy vitamin D 2.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney and the intestinal tract are the principal organs involved in Mg homeostasis. Mutations affecting the intestinal and renal transport of Mg 2+ ions like transient receptor potential cation ( TRPM6 ), pterin-4-alpha carbinolamine dehydratase 1 ( PCBD1 ) or cystathionine-β-synthase-pair domain divalent metal cation transport mediator 2 ( CNNM2 ) gene can lead to HSH 4–6. Hypomagnesaemia causes hypocalcaemia by three mechanisms: end-organ unresponsiveness to PTH, impaired release of PTH and impaired formation of 1,25-dihydroxy vitamin D 2.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, transgenic murine models and the identification of their disorders have provided valuable insights into the molecular mechanisms of renal magnesium absorption [5]. The spectrum of etiologies of hereditary magnesium wasting related to monogenic mutations yielding dysfunctional transporter proteins, is still expanding [1,4,46]. Phenotypic traits alluding to a genetic etiology and warranting advice from the geneticist apart from family history, are features like early-onset hypomagnesemia, dysmorphic characteristics, neurosensorial hearing loss, cognitive dysfunction, epilepsy, diabetes, nephrocalcinosis and biochemical features such as hypercalciuria, metabolic alkalosis, and hypokalemia.…”
Section: Hereditary Etiologies Of Hypomagnesemiamentioning
confidence: 99%
“…Also, the list of etiologies of magnesium deficiency is still expanding. Novel hereditary causes of hypomagnesemia are being deciphered in tight conjunction with the exploration of the various pathways of renal tubular magnesium transport [4,5]. The causal role of commonly used drugs such as proton pump inhibitors or, more rarely, cetuximab (monoclonal antibodies against epidermal growth factor receptor) adds to the increasing list of drugs associated with decreased magnesium absorption or enhanced urinary loss.…”
Section: Introductionmentioning
confidence: 99%
“…The hereditary renal hypomagnesemia is a rare disease that caused by genetic variant-induced dysfunction of magnesium reabsorption in the kidney [1]. Magnesium is one of the most crucial cations in the human body, constituting a variety of enzymes that are involved in DNA synthesis, protein interaction and oxidative phosphorylation [2]. In addition, study has shown that magnesium possesses inhibitory effect on excitability of central nervous system, skeletal muscle and cardiomyocytes [3].…”
Section: Introductionmentioning
confidence: 99%